Promoting University Students' Mental Health: A Systematic Literature Review Introducing the 4M-Model of Individual-Level Interventions - Nair, Bhavana; Otaki, Farah (Frontiers in Public Health, 2021)
Objective: The purpose of this study is to systematically review recently published individual student-level interventions aimed at alleviating the burden of mental health challenges faced by the students and/ or at equipping them with coping mechanism that will foster their resilience. Methods: This study relied on a systematic literature review. PubMed dataset was used; the search was confined to the following period: July 2016-December 2020. Results: A total of 1399 records were identified by the electronic search, out of which 40 studies were included in this study. The authors inductively identified four overlapping categories of interventions across all included articles, and coded them as follows: Mindfulness, Movement, Meaning, and Moderator. Accordingly, each study was linked to at least one of four overlapping categories based on the nature of the intervention(s) under investigation, leading to differing assortments of categories. Conclusions: The 4M-Model generated by this study encourages focusing on devising holistic, university-based interventions that embrace the individuality of students to improve their mental health through elements of mindfulness, movement, meaning, and moderator. Through this focused approach, university counsellors are enabled to design interventions that address students’ physical, psychological, emotional, and social needs.